TECHNICAL CONDITION OF FIXED ASSETS ANALYSIS - M.U.Xajiyev; I.B.Sapayev (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
Fixed assets are in continuous use. Because of this, some of the fixed assets become obsolete, fail, and others are put into use. Consequently, the technical condition of fixed assets has a significant impact on the execution of the product production plan. If the technical condition of the main means is at a satisfactory level, this, in turn, is unlikely to lead to the idleness of equipment and machines, and sometimes to accidents (destruction). Therefore, the main means should be in a technically well-adjusted state. Maintenance of fixed assets at a technically satisfactory level is carried out through current and capital repairs.